Implementasi Model Quantum Learning pada Pendidikan Anak Usia Dini di Raudhatul Athfal An-Nidhomiyah - karina Nur Aini; Sugeng pradikto (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2025)
. This study examines how the Quantum Learning model is used in the Raudhatul Athfal (RA) An-Nidhomiyah class. RA An-Nidhomiyah is an early childhood education center dedicated to raising a generation of Muslims who are highly moral, intellectual, and independent. An innovative method that makes learning fun and efficient is the form of quantum learning. This model combines interactive principles that encourage different learning styles, actively engage students, and consider the developmental needs of children. For example, singing while memorizing, visiting tours, and telling stories while acting out. The findings of the study indicate that the use of Quantum Learning in RA An-Nidhomiyah improves children's memory and motivation to learn while helping them understand moral and spiritual principles in a supportive atmosphere. This study emphasizes the value of innovation. Keywords: Innovation Values, Early Childhood Education and Quantum Learning.